2002
DOI: 10.1007/s00254-001-0446-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ground vibrations caused by bench blasting at Can Open-pit Lignite Mine in Turkey

Abstract: The principal disturbances created by blasting in open-pit mines are vibrations, air blast and fly rock. All of these problems, under some circumstances, may cause severe damage to structures nearby and, apart from that, these can be the possible sources of permanent conflict with the inhabitants who live close to the operation. Therefore, a vibrationcontrol study was performed in mines on the basis that prediction of ground vibration components is of great importance in minimising environmental complaints. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 1 publication
1
19
0
Order By: Relevance
“…According to many researchers (Bureau of Indian Standard 1973;Kahriman 2002;Singh 2004;Singh and Singh 2005;Sawmliana et al 2007), PPV is set as an index for measuring ground vibrations as it is an important indicator for controlling the structural damage criteria. During a few past decades, in order to predict PPV produced by blasting, many vibration predictors have been proposed empirically (e.g., Duvall and Petkof 1959;Langefors and Kihlstrom 1963;Davies et al 1964;Ambraseys and Hendron 1968;Roy 1993).…”
Section: Introductionmentioning
confidence: 99%
“…According to many researchers (Bureau of Indian Standard 1973;Kahriman 2002;Singh 2004;Singh and Singh 2005;Sawmliana et al 2007), PPV is set as an index for measuring ground vibrations as it is an important indicator for controlling the structural damage criteria. During a few past decades, in order to predict PPV produced by blasting, many vibration predictors have been proposed empirically (e.g., Duvall and Petkof 1959;Langefors and Kihlstrom 1963;Davies et al 1964;Ambraseys and Hendron 1968;Roy 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies that employed empirical models to predict peak particle velocity Researcher Comment Kahriman (2002) Analysis of ground vibrations caused by bench blasting Responses of roof and pillars of underground coal mines to vibration induced by adjacent open-pit blasting Kuzu and Ergin (2005) Assessment of environmental impacts of quarry-blasting operation Rai et al (2005) Prediction of maximum safe charge per delay in surface mining Singh et al (2006) Evolution of effective charge weight per delay for prediction of ground vibrations generated from blasting Kuzu (2008) The importance of site-specific characters in prediction models for blast-induced ground vibrations Ak et al (2009) Evaluation of ground vibration effect of blasting operations Table 2. Some studies that employed soft computing techniques to predict peak particle velocity Researcher Comment Chakraborty et al (2004) A fusion neural network for estimation of blasting vibration Singh (2004) Artificial neural network approach for prediction and control of ground vibrations in mines Singh and Singh (2005) An intelligent approach to prediction and control ground vibration in mines Khandelwal and Singh (2006) Prediction of blast induced ground vibrations and frequency in opencast mine Khandelwal and Singh (2007) Evaluation of blast-induced ground vibration predictors Iphar et al (2008) Prediction of blast-induced ground vibration using artificial neural network Khandelwal and Singh (2009) Prediction of ground vibrations resulting from the blasting operations in an open-pit mine by adaptive neuro-fuzzy inference system…”
Section: Site Description and Data Measurementmentioning
confidence: 99%
“…Many researchers [6,[11][12][13][14] have observed that the PPV is used as an index for measuring the ground vibrations as it is an important indicator for controlling the structural damage. During past few decades, many empirical vibration predictor equations have been proposed to calculate the PPV produced by a blast (e.g., [15][16][17][18][19]) using two factors, namely maximum charge per delay and distance from the blast face.…”
Section: Literature Reviewmentioning
confidence: 99%